Engineering metal-based hydrogel-mediated tertiary lymphoid structure formation via activation of the STING pathway for enhanced immunotherapy - Jin, Xiao-Kang; Liang, Jun-Long; Zhang, Shi-Man; Ji, Ping; Huang, Qian-Xiao; Qin, You-Teng; Deng, Xin-Chen; Liu, Chuan-Jun; Zhang, Xian-Zheng (Materials horizons, 2023)
Tertiary lymphoid structures (TLSs) primarily constructed by multiple immune cells can effectively enhance tumor immune responses, but expediting the formation of TLSs is still an enormous challenge. Herein, a stimulator of interferon gene (STING)-activating hydrogel (ZCCG) was elaborately developed by coordinating Zn 2+ with 4,5-imidazole dicarboxylic acid, and simultaneously integrating chitosan (a stimulant of STING pathway activation) and CpG (an agonist of toll-like receptor 9, TLR9) for initiating and activating cGAS-STING and TLR9 pathway-mediated immunotherapy. Moreover, the dual-pathway activation could effectively enhance the infiltration of immune cells and the expression of lymphocyte-recruiting chemokines in the tumor microenvironment (TME), thereby promoting the formation of TLSs and further strengthening tumoricidal immunity. Local administration of the hydrogel could prime systemic immune responses and long-term immune memory and improve the therapeutic effects of programmed death-1 antibody (αPD-1) to inhibit tumor progression, metastasis and recurrence. The engineered hydrogel lays the foundation for tumor immunotherapy strategies based on the enhanced formation of TLSs via the activation of the cGAS-STING and TLR9 pathways.